2017
DOI: 10.21608/jppp.2017.46141
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Damping-off and Root Rot Diseases in Lentil Using kinetin and Trichoderma.

Abstract: Damping-off and root rot diseases caused by several soil-borne pathogenic fungi are the most responsible for high reduction in lentil yield. The aim of the present study is to evaluate the efficiency of kinetin and Trichoderma for controlling these diseases and lentil productivity compared with Rizolex-T50 fungicide. Rhizoctonia solani and Fusarium oxysporum are the common causal pathogens which isolated from infected lentil collected from different fields of Dakahlia Governorate, Egypt. In greenhouse: both te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…The fungus was pathogenic and causing damping-off and root rot diseases in lentil cultivar (Giza9). Such results confirmed the previous findings are reported by Abd El-Hai, et al (2017) Soil amendment with compost is an agronomically increasing practice as well as an attractive waste management strategy. The addition of mature compost to soil favors plant development and improves soil quality, as well as having a suppressive effect on many soils borne plant pathogens (Erhart et al, 1999;Cotxarrera et al, 2002;Abdelhamed et al, 2004 andKumari et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The fungus was pathogenic and causing damping-off and root rot diseases in lentil cultivar (Giza9). Such results confirmed the previous findings are reported by Abd El-Hai, et al (2017) Soil amendment with compost is an agronomically increasing practice as well as an attractive waste management strategy. The addition of mature compost to soil favors plant development and improves soil quality, as well as having a suppressive effect on many soils borne plant pathogens (Erhart et al, 1999;Cotxarrera et al, 2002;Abdelhamed et al, 2004 andKumari et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Damping-off symptoms are yellow seedlings, while no secondary roots or a brown/black tap roots and plant death. (Hamdi and Hassanein,1996;Abdel-Monaim and Abo-Elyousr, 2012;and Abd El-Hai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effects of hydroquinone, salicylic acid, benzoic acid, and chitosan, with regard to Topsin-M 70® fungicide, toward the mycelia radial outgrowth of both examined pathogenic fungi were evaluated In vitro testes. As could be observed in Table (2), all tested abiotic substances led to a significantly lowering of the mycelia radial outgrowth of the two examined fungal pathogens, but to different degrees. Topsin-M 70% was found to be the E3S Web of Conferences 462, 02014 (2023) AFE-2023 https://doi.org/10.1051/e3sconf/202346202014 most effective treatment, with a 100% reduction in the mycelia radial growth for both fungi.…”
Section: Fungal Growth As Affected By Abiotic Substancesmentioning
confidence: 52%
“…It was possible that the effect of the phytopathogenic fungi on chlorophyll and carotenoids was an attenuation of the biosynthetic rate rather than a breakdown of pigments already formed (Elwakil et al, 2009a). This reduction might be attributed to the consequence of the degradation of leaf pigments of plant tissues (Abd El-Hai et al 2017). Kern (1972) reported that the adverse effect of fungal pathogen on chlorophyll pigments may be due to the fact that the fungal toxins form iron-chelate, transforming iron to become unavailable to participate in chlorophyll synthesis.…”
Section: Discussionmentioning
confidence: 99%